Applications of secure multiparty computation - Laud, Peeter; Kamm, Liina (Cryptology and information security series ;, 2015)
Secure multi-party computation (SMC), a cryptographic technology, makes it possible to execute specific programs on confidential data while ensuring that no other sensitive information from the data is leaked. The book will be of interest to all those whose work involves the secure analysis of confidential data.